Comparison of Peripheral Nerve Damages According to Glucose Control Timing in Experimental Diabetes - Jin, H. Y.; Kang, S. M.; Liu, W. Y.; Song, C. H.; Lee, K. A.; Baek, H. S.; Park, T. S. (Experimental and Clinical Endocrinology & Diabetes, 2012)
In addition to tight glucose control, early intensive therapy has been reported to be more important for the prevention of diabetic micro- and macro-vascular complications. What is not known exactly is the quantitative difference according to timing delay in glucose control and whether early period control is really better than late control in terms of diabetic peripheral neuropathy. In this study, we investigated the effect of timing differences in glucose control on the peripheral nerves in an experimental diabetic model.5 groups (6–8 rats in each group) were comprised of normal glucose rats (designated control), rats with hyperglycemia (designated DM), rats with glucose control for the entire 28-week study period (designated DM + INS [W0–28]), rats with glucose control for the early 14-week period followed by hyperglycemia for the late 14-week period (designated DM + INS [W0–14]), and rats with hyperglycemia for the early 14-week period followed by glucose control in the late 14-week period (designated DM + INS [W15–28]).We found that the current perception threshold (CPT) was lower in the DM + INS (W0–28) and DM + INS (W15–28) groups than in the DM + INS (W0–14) or DM groups (P<0.05). The mean myelinated fiber area of the sciatic nerve was significantly greater in the DM + INS (W0–28) and DM + INS (W15–28) groups (63.5±2.32 and 60.1±2.14 um, respectively) than in the DM + INS (W0–14) or DM groups (55.5±2.81 or 51.5±2.64 um, respectively) (P<0.05), and the intraepidermal nerve fiber (IENF) density was significantly higher in the DM + INS (W0–28) and DM + INS (W15–28) groups (6.9±0.46 and 6.8±0.11, respectively) than in the DM + INS (W0–14) or DM groups (59.5±0.32 and 5.3±0.39/mm, respectively) (P<0.05).Our results indicate that continuous glucose control is necessary to alleviate peripheral nerve damage and that glycemic control during the later period may be more important than early period management. The importance of continuous glucose control, including the later period of diabetes, should therefore be emphasized in diabetic peripheral neuropathy.
Keywords: diabetic peripheral neuropathy; intraepidermal nerve fiber density; timing of glucose control